Effectiveness of Injectable Platelet Rich Fibrin, Oxygen Releasing Gel and Hyaluronic Acid Gel as Local Drug Delivery Agents in the Treatment of Chronic Periodontitis: A Clinico-Microbiologic Study - Bansal, Mansi (2026)
This study clinically and microbiologically evaluated the efficacy of liquid i-PRF, oxygen-releasing gel, and hyaluronic acid (HA) gel as local drug delivery (LDD) agents adjunctive to scaling and root planing (SRP) for treating periodontal pockets. A split-mouth randomized controlled trial involved 12 patients with 80 periodontal pockets (3-6 mm depth). Pockets were randomly assigned to four groups: Control (SRP alone), Experimental Group I (i-PRF + SRP), Group II (oxygen-releasing gel + SRP), and Group III (HA gel + SRP). Plaque samples were analyzed for spirochetes using dark-field microscopy at baseline, 1- and 3-months post-treatment. Other primary outcome assessed were Plaque Index (PI), Gingival Index (GI), Probing Pocket Depth (PPD), Clinical Attachment Level (CAL), and Gingival Recession (GR)—were measured using a UNC-15 probe. The statistical tests used were the Bonferroni test for intragroup comparison, the paired t test, the repeated measure analysis of variance test (ANOVA), and the unpaired t test for intergroup comparison between different groups. Intragroup analysis showed significant improvements in PI, GI, PPD, CAL, and GR across all groups (p<0.05). Intergroup comparisons revealed no significant differences. Microbiologically, i-PRF significantly reduced spirochetes (p<0.05), while oxygen-releasing gel showed superior clinical outcomes (p<0.05). All LDD agents have shown significant therapeutic potential.  Oxygen-releasing gel excelled clinically, while i-PRF was microbiologically superior, indicating its therapeutic potential for periodontal pocket treatment.